1996
DOI: 10.1017/s0950268800001242
|View full text |Cite
|
Sign up to set email alerts
|

Are homosexual males a risk group for hepatitis A infection in intermediate endemicity areas?

Abstract: SUMMARYThe purpose of this study was to examine the prevalence of antibody against hepatitis A (anti-HAV) in a population of homosexual men compared with that of heterosexual men in an area of intermediate HAV endemicity (Madrid, Spain). A total of 148 patients were recruited in a Sexually Transmitted Diseases Clinic: 74 homosexuals (mean age of 28 + 5 years) and 74 heterosexuals (29 + 5 years). The prevalence of anti-HAV antibody was 47 % and 43 % for homo-and heterosexuals, respectively. Among the factors ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
3

Year Published

1999
1999
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 9 publications
1
3
0
3
Order By: Relevance
“…However, our findings are in agreement with those previously reported in a Belgian [9] and a Spanish study [8]. In a recent US study, the HAV prevalence among homosexuals was similar to the age-adjusted prevalence estimated for the general United States population [12].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, our findings are in agreement with those previously reported in a Belgian [9] and a Spanish study [8]. In a recent US study, the HAV prevalence among homosexuals was similar to the age-adjusted prevalence estimated for the general United States population [12].…”
Section: Discussionsupporting
confidence: 93%
“…However, some studies have shown that the prevalence of antibodies to HAV (anti-HAV) among homosexual men is similar to that found in heterosexual men [8] and in the general population [9,10].…”
Section: Introductionmentioning
confidence: 92%
“…No such associations were found in this study, possibly due to the widespread nature and collinearity of these practices in the cohort. A well-known risk factor for HAV infection in men who have sex with men, oral-anal sexual contact [Corey and Holmes, 1980;Ballesteros et al, 1996;Katz et al, 1997], could not be evaluated in this analysis, since the risk assessment did not include any questions about this behavior. Isolated anti-HBc was observed in 158 men and more HIV positive men had this serologic pattern than HIV negative men (Table I).…”
Section: Discussionmentioning
confidence: 99%
“…HAV infection incidence among men who have sex with men is greater than in heterosexual men, and cyclic HAV infection outbreaks in men who have sex with men have been reported [Corey and Holmes, 1980;CDC, 1992;Leentvaar-Kuijpers et al, 1995;Katz et al, 1997;CDC, 1998;Bell et al, 2001;Cotter et al, 2003]. Oral-anal contact and insertive anal intercourse facilitate fecal-oral transmission of HAV and are associated with infection [Corey and Holmes, 1980;Ballesteros et al, 1996;Katz et al, 1997]. In the US, men who have sex with men are 10-15 times as likely to be infected with HBV as men in the general population.…”
Section: Introductionmentioning
confidence: 99%
“…A transmissão em homossexuais masculinos tem sido suspeitada e alguns surtos epidêmicos foram registrados nessa população. Alguns estudos têm mostrado que altos níveis de soroprevalência de hepatite A em homens homossexuais estão mais relacionadas com contacto oral-anal do que com a orientação sexual 4 .…”
Section: As Formas De Transmissão Do Vhaunclassified